Onus and quantum of proof for breaching the standard of procedure during the movement control order - Mohamad Ismail Mohamad Yunus (Penerbit Universiti Kebangsaan Malaysia, 2021)
The objective of this research paper is to highlight on the issues relating to the onus and quantum of proof for breaching the standard of procedure (SOP) during the movement control order (MCO) due to Pandemic Covid 19 in Malaysia. In tackling the issues, the research methodology applied by the author is by analysing and evaluating some decided cases, studying the substantive laws, regulations, and procedure in enforcing movement control order. The contemporary legal issues in this article are on whom the onus (burden) of proof lies and what is the quantum (standard) of proof required for the offence of breaching social distancing during the movement control order, be it conditional, restricted or recovery. The standard of procedure always changing based on the types of movement control order made by the Federal Government. In the New Straits Times dated 4 April 2021, it was reported that 17 publics were compounded for not practicing social distancing. Many questions raise as what is the real meaning of social distancing? In which type of offence, the social distancing offence lies on? What are the elements that will constitute the offence? As to the remedies, the author has submitted the nature of the offence for breaching the SOP during MCO. The expectation result of this paper is to give a clear picture as to the matter of standard of proof and burden of proof that to be considered by the trial court in deciding the issue of breaching SOP. The significance of this paper is to point out some contemporary identical legal issues relating to SOP during MCO. The issues will be highlighted in this article.